2019
DOI: 10.6023/cjoc201901037
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Quinazolinone Derivatives Catalyzed by Alkaline Protease

Abstract: Alkaline protease-catalyzed synthesis of quinazolinone derivatives was developed between β-keotester and o-aminobenzamide. Because ethanol is one kind of eco-friendly solvents, this method can reduce the impact of solvents on the environment. Alkaline protease as a biocatalyst has many advantages, e.g. high catalytic activity, environmentally friendly, wide variety of sources and simple operation. In addition, a variety of quinazolinone derivatives was obtained with good to excellent yields just using 2000 U a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 7 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…From the viewpoint of green chemistry, the field of biocatalysis is attracting increasing attention. Enzymes are green and efficient biocatalysts [12], we have reported several studies on the synthesis of quinazolinone derivatives using pepsin [13], and alkaline [14] protease as catalysts. Thus, it is necessary to explore newer synthetic strategies for quinazolinones.…”
Section: Introductionmentioning
confidence: 99%
“…From the viewpoint of green chemistry, the field of biocatalysis is attracting increasing attention. Enzymes are green and efficient biocatalysts [12], we have reported several studies on the synthesis of quinazolinone derivatives using pepsin [13], and alkaline [14] protease as catalysts. Thus, it is necessary to explore newer synthetic strategies for quinazolinones.…”
Section: Introductionmentioning
confidence: 99%
“…14 Additionally, it is the advantages of these enzymes that are frequently reported in organic reactions catalyzed by enzymes. [15][16][17][18][19][20] Due to the aforementioned properties possessed by enzymes, researchers are currently focusing on the combination of enzymes and conventional catalysts to develop organic reactions that cannot be achieved by a single catalyst, such as photoenzymatic ones. [21][22][23] As a well-studied hydrolase, -chymotrypsin has been demonstrated that it can keep its activity in organic solvents.…”
mentioning
confidence: 99%